STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN HAFALAN AL-QUR’AN SISWA DI SMP ISLAM SABILURROSYAD MALANG - Sabrina Yazid Baktayan; Anwar Sa’dullah; Muhammad Fahmi Hidayatullah (VICRATINA, 2021)
This study describes the strategy of Islamic religious education teachers in improving the students' memorization of the Qur'an at Islamic Junior High School Sabilurrosyad Malang. The focus of the research is on learning to memorize the Qur'an and the strategy of Islamic religious education teachers in improving the memorization of the Qur'an at Islamic Junior High School Sabilurosyad Malang and discussing the inhibiting factors and supporting factors for the implementation of Islamic Religious Education teachers in improving the memorization of the Qur'an. This study uses a qualitative descriptive. The search for data in this study used three methods, namely observation, unstructured interviews, and documentation. The results of this study indicate that: Students are able to read the Qur'an correctly and it is proven by passing the Bil Qolam method and at least memorizing 3 Juz so that before they enter tahfidz students are tahsin first. As for the strategy used in learning to memorize the Qur'an, namely using the sorongan or individual (private) method for grades 8 and 9 using muroja'ah for 7th grade money which still uses the talaaqi method. The obstacles in memorizing the Qur'an are low learning motivation, students are lazy to memorize, friends who are less supportive, students think memorization is difficult and are late to enter class.